THE IMPLEMENTATION OF SCRAPBOOK AS A MEDIA TO TRAIN STUDENTS’ SCIENCE LITERACY IN STATIC FLUID - EKA YUNIAR, RISA; SUPRAPTO, NADI (Inovasi Pendidikan Fisika, 2019)
The research aims to describe science literacy learning and students learning response toward implementation of the scrapbook as a media to train science literacy in the static fluid. The type of research is Pre Experimental with One-group pretest-posttest design. The samples in this research are students of experiment class. Observation sheet, questionnaire, and documentation guidance are used to collect data. Observation analyzed to describe science literacy learning and questionnaire response. Based on the data analyzed, the implementation of the scrapbook as media was done very well. Students response to the implementation of the scrapbook as a media had good criteria.Keywords: Scrapbook, Literacy science, students learning response.